Combined ATR and DNA-PK Inhibition Radiosensitizes Tumor Cells Independently of Their p53 Status - Hafsi, Hind; Dillon, Magnus T.; Barker, Holly E.; Kyula, Joan N.; Schick, Ulrike; Paget, James T.; Smith, Henry G.; Pedersen, Malin; McLaughlin, Martin; Harrington, Kevin J. (Frontiers in Oncology, 2018)
Head and neck squamous cell carcinoma (HNSCC) is a significant cause of cancer deaths. Cisplatin-based chemoradiotherapy is a standard-of-care for locally advanced disease. ATR and DNA-PK inhibition are actively being investigated in clinical trials with preclinical data supporting clinical translation as radiosensitizers. Here, we hypothesized that targeting both ATR and DNA-PK with small molecule inhibitors would increase radiosensitization of HNSCC cell lines. Radiosensitization was assessed by Bliss independence analysis of colony survival data. Strong cell cycle perturbing effects were observed with ATR inhibition reversing the G2/M arrest observed for radiation-DNA-PK inhibition. Increased apoptosis in combination groups was measured by subG1 DNA populations. DNA-PK inhibition increased radiation-induced RAD51 and gamma-H2Ax foci, with the addition of ATR inhibition reducing levels of both. A sharp increase in nuclear fragmentation after aberrant mitotic transit appears to be the main driver of decreased survival due to irradiation and dual ATR/DNA-PK inhibition. Dual inhibition of DNA-PK and ATR represents a novel approach in combination with radiation, with efficacy appearing to be independent of p53 status. Due to toxicity concerns, careful assessment is necessary in any future translation of single or dual radiosensitization approaches. Ongoing clinical trials into the ATR inhibitor AZD6738 plus radiation, and the phenotypically similar combination of AZD6738 and the PARP inhibitor olaparib, are likely to be key in ascertaining the toxicity profile of such combinations.